Analysis of The Design Concept for Handling Quarter-Life Crisis with The Qurani Approach - Ratu Bilqis Assyifa (Proceeding International Conference on Religion, Science and Education, 2023)
Every human being will certainly design his future, both in terms of work and love. Some research results show that the quarter-life crisis which is a problem of excessive anxiety is experienced in the late adolescent phase towards the early adult phase. This study seeks to analyze and design quarter-life crisis responses. The method used in this research is qualitative with a case study approach. Data sources consist of nine primary data and two secondary data. The results of the study show that three problems can cause a person to be in a quarter-life crisis, including a humanizing crisis using the Quranic approach Q.s Al-Insan verses 29-31. Crisis role model with the Quranic approach Q.s. Al-Ahzab verse 21. And the crisis of al-hikmah with the approach of the Qurani Q.s. Al-Baqarah verse 269. This study recommends that trials be carried out to apply this countermeasures design in practice in everyday life.